Comparison of Laparoscopic versus Open Appendicectomy - Hossain, SM Shahadat; Jahan, Farhana Israt; Rahman, Munshi M Mujibur; Azad, Md Abdus Samad Al; Rahman, Md Shahinur; Hossain, SM Shakhwat (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: The advent of laparoscopic surgery has dramatically changed the field of surgery. With improvements in the equipment and increasing clinical experience it is now possible to perform almost any kind of procedure under laparoscopic visualization. The idea of minimal surgical trauma, resulting in significantly shorter hospital stay, less postoperative pain, faster return to daily activities, and better cosmetic outcome have made laparoscopic surgery for acute appendicitis very attractive. Objective: The aim of the present study was to compare the laparoscopic approach and the conventional technique in the treatment of acute appendicitis. Method: This prospective randomized clinical trial was conducted at CMH, Savar Cantonment and Navy Hospital, BNS Patenga, Chittagong. A total of 86 patients who underwent appendicectomy during December 2009 to March 2011 were included in this study. A total of 40 patients had laparoscopic appendicectomy and 46 underwent open procedure. Clinical outcome measures were compared between the two groups with respect to several variables. Results: Among the study population, the operating time was shorter for the OA patients than for the LA patients (LA, 35 min vs. OA, 30 min; p value 0.33), which is not statistically significant. The differences in hospital stay of 4 days for the LA group and 8 days for the OA group and p value 0.01 which is statistically significant. Return to oral diet was same in both groups with no statistical difference LA, 20 h vs. OA, 22 h; return to work LA was 14 days vs. OA 18 days. Although the rate for overall complications was lower in the LA group 5% vs. 18% in OA; p value 0.001 which is statistically significant. Conclusion: The laparoscopic approach to appendicectomy in patients with acute appendicitis does offer a significant advantage over the open approach in terms of length of hospital stay, postoperative complications, or quality of life, which are considered as the major advantages of minimally invasive surgery. Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014